PENGARUH DURASI CAMSHAFT TERHADAP PRESTASI MESIN BENSIN 110 CC - Halim Halim; Reza Bachmid; Sabdha Purna Yudha (Otopro, 2021)
Effect camshaft duration on performance of 110 cc gasoline engine carried out by comparing the duration of standard and modified camshafts of 303.5o to obtain maximum power produced by 110 cc smash type Suzuki engine and its effect on fuel consumption. This study aims to know of, (1) torque machine with modification in duration camshaft, (2) knowing total fuel consumption (FC), spesific fuel consumption (SFC), and thermal efficiency of the standard engine and engine has modified in the duration of its camshaft. A method of testing in the research was done with to the chassis of dynamometer as for testing done in PT.Suzuki galesong pratama through adhering to a standard testing suzuki that has been set. The results showed a change in the value of power and torque on standard engine power obtained by 5.3 HP or 3.88 kW to 6.0 HP or 4.63 kW with a torque value of 6.14 N.m, then decreased at 9000 rpm rotation of 5.02 Nm. While the duration of power modification camshaft obtained is 7.5 HP or 5.60 kW with a torque of 8.65 Nm, it also decreases at 9000 rpm of 7.9 HP or 5.89 kW. The significant effect occurs at 9000 rpm. Standard camshaft FC value is obtained at 0.8946 kg / h, SFC = 0.1932 kg / kWh. For duration of modified camshaft, at 9000 rpm,  FC value obtained was 1.6526 kg / h, SFC = 0.2806 kg / kWh. From these results, it is known that an increase occurred in the FC value with a difference of 0.758 from previous results with an SFC of 0.0874. Furthermore, thermal efficiency obtained by 50.01% at 6000 rpm decrease by 40.29 % at 9000 rpm for standard camshaft. The duration of a modified camshaft was obtained by 53.34% at 6000 rpm and decrease by 30.02 %  at 9000 rpm.